Impact of a 12-week obesity intervention on menopausal symptoms and psychological well-being across menopause stages: a cross-sectional analysis - Rupal Kumar; Moattar Raza Rizvi; Waqas Sami (Frontiers in Reproductive Health)
IntroductionMenopause poses unique physical and psychological challenges, especially for obese women, impacting quality of life across menopausal stages. This study evaluates a 12-week obesity educator program on body composition, menopausal symptoms, and psychological well-being among pre-, peri-, and post-menopausal obese women in Delhi NCR, India.MethodsA cross-sectional analysis was conducted with 291 obese women (97 per menopausal stage) assessing anthropometric measures, menopausal symptoms via the Menopause Rating Scale (MRS), and psychological well-being using the Well-being Questionnaire (W-BQ12). Data were analyzed using paired t-tests, ANCOVA, Pearson's correlation, and regression analysis.ResultsThe intervention led to significant weight reduction across all groups (3.8–4.5 kg, p < 0.001), waist circumference decreases (5.7–6.5 cm, p < 0.001), and HbA1c reductions by 0.4% (p < 0.001). Regression analysis identified waist-to-hip ratio and hemoglobin as predictors of somato-vegetative and psychological symptoms (R2 = 0.15, p < 0.05). MRS scores showed the most improvement in perimenopausal women.ConclusionThe obesity educator program effectively improved body composition, glycemic control, and well-being across menopausal stages, highlighting the value of personalized interventions for menopausal health management.